Penetapan Metode Sig Sixma dalam Proses Pengendalian Mutu Produk Ikan Tuna Yellowfin (Thunnus albacares) Kaleng di PT. XYZ - Sabdania Sabita; A.S.F.Q.R Mubarok; B. Kusuma; A.W. Perdana (STIKes Ibnu Sina Ajibarang, 2024)
Yellowfin tuna (Thunnus albacares) is a type of large pelagic fish that is spread in tropical and subtropical oceans throughout the world and is a leading export commodity of Indonesia. This field work practice aims to increase insightknowledge, skills, and experience in the tuna canning process. PT. XYZ is a company engaged in the export of fishery products in the form of tuna in cans. The processing process carried out begins with receiving raw materials, washing and thawing, cutting, then cooking, showering. Furthermore, pre-cleaning and cleaning, metal detecting, filling meat, filling medium, closing cans, sterilization, incubation, labeling and packing, and the stuffing process are carried out. The quality control method used is sig sixma, where the resulting DPMO value is 6.41 and sigma 440.382. Meanwhile, the control chart calculations obtained central line (CL) results, namely points 3,4, and 5. Meanwhile, points 6, 7, and 10 were above the central line (CL) and points 1, 2, 8, and 9 were below the center line (CL). Then the Paretto diagram shows that 31%, 45% of can lid scratch damage, and 60% of can body scratch damage.